Explaining Current Fertility Dynamics in Tropical Africa From an Anthropological Perspective: A Cross-Cultural Investigation. (July 2016) - Korotayev, Andrey; Zinkina, Julia; Goldstone, Jack; Shulgin, Sergey
Tropical Africa is known to be lagging far behind the rest of the world in its fertility transition. Many attempts have been made to specify the factors responsible for its resistance to fertility decline; however, no systemic explanation of the mechanisms sustaining its high fertility has been presented in cross-cultural perspective. In this article, we show how a set of anthropological factors provides both social and economic foundations for the preservation of high fertility in tropical Africa. Cross-cultural tests imply that the most important obstacles to tropical Africa's fertility transition are (a) a high ideal family size, (b) a large potential to absorb increases in the female labor force participation rate without any substantial decreases in fertility due to ample child care readily available through extended family structures, (c) a large potential to increase fertility at the early stages of economic development through the abolition of postpartum sex taboos, and (d) a low potential for increases in birth spacing to contribute to fertility decline. In the last section, we discuss how the results obtained could be useful for policy recommendations aimed at accelerating the fertility decline in tropical Africa, and mitigating the forecasts of explosive population growth.